Reflection on pedagogical practice, through an electronic portfolio, in initial teacher training (Educational Knowledge, 2026)
This action research study was conducted within the context of the final teaching practicums of students from three Education programs. The main objective was to promote pedagogical reflection within their professional practice through an electronic portfolio. Data was collected through focus groups, structured interviews, and documentation. The results showed that the frequency and levels of reflection did not change significantly; however, the students recognized the electronic portfolio as a useful tool that aids them in their practicum processes. Based on these findings, it is concluded that addressing the obstacles to pedagogical reflection among students is a priority, and that such reflection should be promoted throughout their training.